Digital crime, trauma, and abuse: Internet safety and cyber risks for adolescents and emerging adults in the 21st century. Issue 1 (2nd January 2021) - Paat, Yok-Fong; Markham, Christine
ABSTRACT: The shift in the technology landscape has altered the technology ecosystem of adolescents and emerging adults in the 21 st century. Yet, with greater use of digital gadgets comes greater mental health risks that technological advancement brings. This study provides a narrative review of contemporary cyber risks faced by adolescents and emerging adults. In particular, this review will cover dangers and effects of cyber-bullying, social media, cyber-dating violence, sextortion, sexting, revenge porn, online dating, catfishing, and scammers, with an emphasis to raise awareness and encourage proactive efforts dedicated to address these social concerns as the digital era continues to evolve.